Viscoelastic testing reveals normalization of the coagulation profile 12 weeks after severe COVID-19 - Abakar Magomedov (Nature Portfolio, 2021)
Abstract COVID 19 is associated with a hypercoagulable state and frequent thromboembolic complications. For how long this acquired abnormality lasts potentially requiring preventive measures, such as anticoagulation remains to be delineated. We used viscoelastic rotational thrombelastometry (ROTEM) in a single center cohort of 13 critical ill patients and performed follow up examinations three months after discharge from ICU. We found clear signs of a hypercoagulable state due to severe hypofibrinolysis and a high rate of thromboembolic complications during the phase of acute illness. Three month follow up revealed normalization of the initial coagulation abnormality and no evidence of venous thrombosis in all thirteen patients. In our cohort the coagulation profile was completely normalized three months after COVID-19. Based on these findings, discontinuation of anticoagulation can be discussed in patients with complete venous reperfusion.